Cauda Equina and Filum Terminale Arteriovenous Fistulas: Anatomic and Radiographic Features - Namba, K. (AJNR Am J Neuroradiol, 2020)
Intradural AVF below the conus medullaris may develop either on the filum terminale or the cauda equina (lumbosacral and coccygeal radicular nerves). Although not a few filum terminale AVFs are found in the literature, only 3 detailed cauda equina AVFs have been reported. Here, we analyze the angiographic and MR imaging findings of our cauda equina and filum terminale AVF cases, supplemented with literature research to characterize the radiologic features of the 2 entities. On angiography, filum terminale AVFs were invariably supplied by the extension of the anterior spinal artery accompanied by a closely paralleling filum terminale vein. Cauda equina AVFs were fed by either a radicular or a spinal artery or both arteries, often with a characteristic wavy radicular-perimedullary draining vein. On thin-section axial MR imaging, the filum terminale AVF draining vein joined the spinal cord at the conus medullaris apex, but that of the cauda equina AVF joined above the conus medullaris apex.